A Review of Various Data Compression Techniques for Secured Data Transfer - Pandey, Aarti (International Journal of Advanced Science and Technology, 2019)
This paper presents a review kind of data compression techniques. Data compression is widely used by the community because through a compression we can save storage. Data compression can also speed up a transmission of data from one person to another. In performing a compression requires a method of data compression that can be used, the method can then be used to compress a data. Data that can be compressed not only text data but can be images and video. This paper explains how a method works in doing a compression and explains which method is well used in doing a data compression in the form of text. The output generated in doing a can be known through the compression file size that becomes smaller than the original file.